Identitas Sosial, Kompleksitas Identitas, dan Sinodalitas: (Suatu Kajian Lintas Iman dalam Konteks Moderasi Beragama di Indonesia) - Yongki Saputra; Juliana Sriana Sinaga (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the dynamics of interfaith relations in Indonesia by integrating Social Identity Theory (SIT), Social Identity Complexity (SIC), and Pope Francis’ vision of synodality. The focus is directed toward understanding how social identity categories, overlapping identity structures, and the synodal vision of communion, participation, and mission enrich the paradigm of religious moderation in a plural society. This research employs a qualitative library research design using descriptive-analytical and content analysis techniques on identity theories, empirical findings on interfaith tolerance, and relevant Catholic Church documents. The analysis includes an exploration of the core concepts of SIT and SIC, a review of interfaith tolerance practices in Indonesian communities, and an examination of the pastoral significance of synodality as a dialogical approach. The findings indicate that religious moderation can flourish when religious communities have natural spaces of encounter, develop flexible identity intersections, and engage actively in mutual listening as emphasized in the Synod 2021–2024. In this context, synodality provides a theological and pastoral framework for cultivating inclusive, creative, and transformative interfaith relations, allowing each religious tradition to express its uniqueness while fostering fraternal harmony.